KAJIAN TEKNIS DISAIN BADAN KAPAL UNTUK PERAIRAN DANGKAL DI KAWASAN LAHAN GAMBUT - Budi Santosa, Ari Wibawa (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2006)
The aim of this research is to solve the river boat’s problem, specially for hinterland waters, that’s not suitable for a big ship, because the width and depth’s water are limited. This design of the Water Bus with twinhull model should be able to reduce the wave caused by moving ship ( Low wash displacemen craft ) and will not silt up for the river, caused by scrapping around the river.